Irritant contact dermatitis caused by sap of rengas - Betty Ekawati Suryaningsih (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Irritant contact dermatitis (ICD) is an inflammation of skin caused by direct cytotoxic effects of chemical, physical or biological agents on epidermal cells without a presence of specific antibody production. It was reported that a 40-year-old man, complaining of itching and a burned sensation on his skins accompanied by pain after contaminated by sap of Rengas. Diagnosis of ICD was established by history taking and physical examination: there are erythematous, multiple, discrete papules, partly necrotic-erythematous skin base on his forearm and right lower abdomen. The patient was treated with mometasone furoate smeared and antihistamines once a night. A characteristic of the sap is black on its woods. Compounds of the sap contain ursiol, rengol, glutarengol, laccol and thitsiol that are irritants causing the ICD.